Organic thin film, organic electroluminescence element, material for organic electroluminescence element, display device and lighting device
Patent Information
- Application Number
- JP2021050648
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-03-24
AI Technical Summary
【0020】 本発明によれば、蒸着プロセスで製造でき、有機EL素子の駆動電圧を低減でき、駆動安定性を向上可能な有機薄膜、並びに、蒸着プロセスに適用でき、有機EL素子の駆動電圧を低減でき、駆動安定性を向上可能な有機EL素子用材料を提供することができる。 また、本発明によれば、前記有機薄膜又は有機EL素子用材料を用いた、駆動電圧が低く、駆動安定性に優れた有機EL素子、並びに、該有機EL素子を具えた表示装置及び照明装置を提供することができる。
Smart Images

Figure 0007644638000019 
Figure 0007644638000020 
Figure 0007644638000021
Abstract
Description
[Technical field]
[0001] The present invention relates to an organic thin film, an organic electroluminescence (hereinafter, electroluminescence (field emission) may be abbreviated as "EL") element, a material for an organic electroluminescence element, a display device, and a lighting device. [Background technology]
[0002] Organic EL elements are thin, soft, and flexible. Furthermore, displays using organic EL elements are capable of displaying images with higher brightness and higher resolution than the currently mainstream liquid crystal display devices and plasma display devices. Furthermore, displays using organic EL elements have a wider viewing angle than liquid crystal display devices. For this reason, displays using organic EL elements are currently being used more widely as displays for televisions and mobile phones. Furthermore, organic EL elements are expected to be used as lighting devices.
[0003] In the case of displays using organic EL elements, there are two manufacturing processes: the (printing) coating process and the vacuum deposition process. Currently, in order to produce products that operate at a low voltage and have a long life, manufacturers generally use the vacuum deposition process, in which materials are heated under high vacuum to sublimate and form a film on the substrate. In organic EL elements, a method is widely used in which a p-type dopant material is added to improve hole injection performance when holes are injected into the organic layer from an anode such as ITO.
[0004] Common hole injection materials include materials that form charge transfer complexes with host materials due to their deep LUMO (lowest energy of conduction band) levels, such as 2,3,5,6-tetrafluoro-7,7,8,8-tetracyano-quinodimethane and molybdenum oxide, and materials that have strong acidic dopants such as sulfonic acid added, such as poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS). Among these, the use of an acidic dopant makes it possible to lower the hole injection barrier from the anode to the organic film, regardless of the HOMO (highest energy of valence band) level of the host material that can transport holes, and has the advantage of broadening the selection of materials that can be used.
[0005] However, it has been confirmed that sulfonic acid-containing materials dissolve the ITO anode, which is the lower electrode, due to their high acidity, and the dissolved indium ions migrate to the vicinity of the light-emitting layer, thereby impairing the operating life of the element (Non-Patent Document 1). [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Sung Jin Jo et al., J. Appl. Phys., 103, 114502 (2008) Summary of the Invention [Problem to be solved by the invention]
[0007] In addition, many acidic materials have the problems of being easily dehydrated and decomposed by heating, which impairs the performance of the material, and being highly hygroscopic and poor in storage. In particular, dopants containing sulfonic acid or trifluoromethanesulfonyl (Tf) groups, which have high electron-withdrawing properties, are easily decomposed and eliminated by heat, making it difficult to apply the deposition process. For this reason, there have been no reports of acidic dopant materials that can be stably stored and deposited, have low driving voltages, and can improve driving stability.
[0008] Therefore, an object of the present invention is to solve the above-mentioned problems of the conventional technology, and to provide an organic thin film that can be produced by a vapor deposition process, capable of reducing the driving voltage of an organic EL element, and capable of improving the driving stability, as well as a material for an organic EL element that can be applied to a vapor deposition process, capable of reducing the driving voltage of an organic EL element, and capable of improving the driving stability. Another object of the present invention is to provide an organic EL element using the organic thin film or the material for an organic EL element, and a display device and a lighting device including the organic EL element. [Means for solving the problem]
[0009] In order to solve the above problems, the present inventors have conducted various studies on acidic materials that can be added to a hole injection layer located between the anode and the light-emitting layer of an organic EL element to improve both the hole injection performance and driving stability of the organic EL element, and that can be formed into a film by a vacuum deposition method. As a result, they have come to the conclusion that an acidic material containing a specific fluorobenzoic acid structure or a fluoronaphthalenedicarboxylic acid structure is suitable for manufacturing an organic EL element by a deposition process, and that by using the acidic material containing the fluorobenzoic acid structure or the fluoronaphthalenedicarboxylic acid structure as an acidic dopant in the hole injection layer of an organic EL element, the driving voltage of the organic EL element to which the deposition process is applied is reduced and the driving stability is improved, thereby solving the above problems, and have arrived at the present invention. The gist of the present invention for solving the above problems is as follows.
[0010] The organic thin film according to one embodiment of the present invention is characterized in that it is a single film including a first material, which is a tetrafluorobenzoic acid derivative having a structure represented by the following general formula (1), and a second material that transports holes, or a laminated film including a film including the first material and a film including the second material. [ka] (In general formula (1), R 1represents an aromatic hydrocarbon group, an aromatic heterocyclic group, an aryl alkylene group, a divalent or trivalent cyclic hydrocarbon group which may have a substituent, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a sulfur atom. n is an integer of 2 to 6. Such an organic thin film can be produced by a vapor deposition process, and by applying it to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved.
[0011] In a preferred embodiment of the organic thin film of the present invention, the first material is a tetrafluorobenzoic acid derivative in which n in the above general formula (1) is 2 or 3. In this case, by applying it to an organic EL element, the driving voltage of the organic EL element can be further reduced and the driving stability can be further improved.
[0012] The organic electroluminescence device according to one embodiment of the present invention has a light-emitting layer between a cathode and an anode, The present invention is characterized in that a layer containing a first material, which is a tetrafluorobenzoic acid derivative having a structure represented by the following general formula (1), is provided between the anode and the light-emitting layer. [ka] (In general formula (1), R 1 represents an aromatic hydrocarbon group, an aromatic heterocyclic group, an aryl alkylene group, a divalent or trivalent cyclic hydrocarbon group which may have a substituent, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a sulfur atom. n is an integer of 2 to 6. Such an organic electroluminescence device can be manufactured by a deposition process, and has a low driving voltage and excellent driving stability.
[0013] Here, it is preferable to have a laminated film of a layer containing the first material and a layer containing a second material that transports holes between the anode and the light-emitting layer, which further reduces the driving voltage and further improves driving stability.
[0014] a layer including the first material and a second material that transports holes between the anode and the light-emitting layer; It is also preferable to have a layer containing the second material between the light-emitting layer and the layer containing the first material and the second material, which also further reduces the driving voltage and improves driving stability.
[0015] In addition, the organic thin film according to another embodiment of the present invention is characterized in that it is a single film including a first material that is a fluoronaphthalenedicarboxylic acid derivative having a structure represented by the following general formula (2) and a second material that transports holes, or a laminated film including a film including the first material and a film including the second material. [ka] (In general formula (2), R 2 and R 3 one of the groups is a carboxyl group, and the other is a fluorine group, a trifluoromethyl group, a cyano group, or a nitro group. Such an organic thin film can be produced by a vapor deposition process, and by applying it to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved.
[0016] A material for an organic electroluminescence device according to one embodiment of the present invention is characterized by containing a fluoronaphthalenedicarboxylic acid derivative having a structure represented by the following general formula (2). [ka] (In general formula (2), R 2 and R 3 one of the groups is a carboxyl group, and the other is a fluorine group, a trifluoromethyl group, a cyano group, or a nitro group. Such a material for organic electroluminescence devices can be applied to a vapor deposition process, and by applying it to an organic EL device, the driving voltage of the organic EL device can be reduced and the driving stability can be improved.
[0017] The organic electroluminescence device according to another embodiment of the present invention has a light-emitting layer between a cathode and an anode, The present invention is characterized in that a layer containing the above-mentioned material for an organic electroluminescence device is provided between the anode and the light-emitting layer. Such an organic electroluminescence device can be manufactured by a deposition process, and has a low driving voltage and excellent driving stability.
[0018] A display device according to the present invention includes the organic electroluminescence element described above. The display device according to the present invention has a low driving voltage and excellent driving stability.
[0019] The present invention also provides a lighting device comprising the organic electroluminescence element described above. The lighting device of the present invention has a low driving voltage and excellent driving stability. Effect of the Invention
[0020] According to the present invention, it is possible to provide an organic thin film that can be produced by a vapor deposition process, capable of reducing the driving voltage of an organic EL element, and capable of improving the driving stability, as well as a material for an organic EL element that can be applied to a vapor deposition process, capable of reducing the driving voltage of an organic EL element, and capable of improving the driving stability. Furthermore, according to the present invention, it is possible to provide an organic EL element which uses the organic thin film or the material for an organic EL element and has a low driving voltage and excellent driving stability, and a display device and a lighting device which include the organic EL element. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an example of an organic EL element of the present invention. [Diagram 2] 19F-NMR spectrum of the compound represented by structural formula (3). [Diagram 3] 1H-NMR spectrum of the compound represented by structural formula (3). [Figure 4]19F-NMR spectrum of the compound represented by structural formula (4). [Diagram 5] 1H-NMR spectrum of the compound represented by structural formula (4). [Figure 6] 1 is a graph showing the relationship between the applied voltage and the luminance of the organic EL elements produced in Examples 1 to 3 and Comparative Example 1. [Figure 7] 1 is a graph showing the change over time in luminance of the organic EL elements produced in Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The organic thin film, the organic electroluminescence device, the material for the organic electroluminescence device, the display device and the lighting device of the present invention will be illustrated in detail below with reference to their embodiments.
[0023] [Organic thin films, materials for organic electroluminescence devices] The organic thin film according to one embodiment of the present invention is characterized in that it is a single film including a first material, which is a tetrafluorobenzoic acid derivative having a structure represented by the following general formula (1), and a second material that transports holes, or a laminated film including a film including the first material and a film including the second material. [ka] (In general formula (1), R 1 represents an aromatic hydrocarbon group, an aromatic heterocyclic group, an aryl alkylene group, a divalent or trivalent cyclic hydrocarbon group which may have a substituent, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a sulfur atom. In the general formula (1), n is an integer of 2 to 6.
[0024] In addition, the organic thin film according to another embodiment of the present invention is characterized in that it is a single film including a first material that is a fluoronaphthalenedicarboxylic acid derivative having a structure represented by the following general formula (2) and a second material that transports holes, or a laminated film including a film including the first material and a film including the second material. The material for an organic electroluminescence device of the present invention is characterized by containing a fluoronaphthalenedicarboxylic acid derivative having a structure represented by the following general formula (2). [ka] (In general formula (2), R 2 and R 3 one of the groups is a carboxyl group, and the other is a fluorine group, a trifluoromethyl group, a cyano group, or a nitro group.
[0025] The tetrafluorobenzoic acid derivative having the structure represented by the general formula (1) and the fluoronaphthalenedicarboxylic acid derivative having the structure represented by the general formula (2) are not easily decomposed by heating and have excellent storage stability, and therefore can be applied to a vapor deposition process. Furthermore, the tetrafluorobenzoic acid derivative having the structure represented by the general formula (1) and the fluoronaphthalenedicarboxylic acid derivative having the structure represented by the general formula (2) have lower acidity than the strongly acidic dopants such as the above-mentioned sulfonic acids, and are less likely to dissolve the anode made of ITO, etc., which is the lower electrode. Therefore, by applying the tetrafluorobenzoic acid derivative having the structure represented by the general formula (1) and / or the fluoronaphthalenedicarboxylic acid derivative having the structure represented by the general formula (2) to an organic EL element, the driving stability of the organic EL element can be improved. In addition, the organic thin film of the present embodiment contains a second material that transports holes. Since the second material transports holes, for example, by disposing the organic thin film between the light-emitting layer and the anode of an organic EL element, the hole injection performance can be improved and the driving voltage of the organic EL element can be reduced. Therefore, the organic thin film of this embodiment can be manufactured by a vapor deposition process, and by applying it to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved. Also, the material for organic electroluminescence elements of this embodiment can be applied to a vapor deposition process, and by applying it to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved.
[0026] R in the above general formula (1) 1 represents an aromatic hydrocarbon group which may have a substituent, an aromatic heterocyclic group, an aryl alkylene group, a divalent or trivalent cyclic hydrocarbon group, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a sulfur atom. The aromatic hydrocarbon group and aromatic heterocyclic group preferably have 3 to 30 carbon atoms, more preferably have 4 to 24 carbon atoms, and further preferably have 5 to 20 carbon atoms. Examples of aromatic hydrocarbon groups include compounds consisting of only one aromatic ring, such as benzene; compounds in which multiple aromatic rings, such as biphenyl and diphenylbenzene, are directly bonded to each other via one carbon atom; and groups formed by removing one to three hydrogen atoms from any of the aromatic rings of condensed ring aromatic hydrocarbon compounds, such as naphthalene, anthracene, phenanthrene, and pyrene. Examples of the aromatic heterocyclic group include compounds consisting of only one aromatic heterocycle, such as thiophene, furan, pyrrole, oxazole, oxadiazole, thiazole, thiadiazole, imidazole, pyridine, pyrimidine, pyrazine, and triazine; compounds in which a plurality of compounds consisting of only one aromatic heterocycle are directly bonded to each other via one carbon atom (such as bipyridine); and groups obtained by removing 1 to 3 hydrogen atoms from any of the aromatic heterocycles of condensed ring heteroaromatic hydrocarbon compounds, such as quinoline, quinoxaline, benzothiophene, benzothiazole, benzimidazole, benzoxazole, indole, carbazole, dibenzofuran, dibenzothiophene, thieno[2,3-d]thiophene, acridine, and phenanthroline. The arylalkylene group includes a group formed by combining the above aromatic hydrocarbon group with an alkylene group having 1 to 3 carbon atoms. The divalent or trivalent cyclic hydrocarbon group preferably has 3 to 12 carbon atoms, and more preferably has 3 to 6 carbon atoms. Also, R 1may be a group formed by combining two or more of the above aromatic hydrocarbon groups, aromatic heterocyclic groups, aryl alkylene groups, and divalent or trivalent cyclic hydrocarbon groups. Furthermore, R 1 may be a group formed by combining one or more of the above aromatic hydrocarbon groups, aromatic heterocyclic groups, aryl alkylene groups, and divalent or trivalent cyclic hydrocarbon groups with a sulfur atom. Examples of such groups include diaryl sulfides such as diphenyl sulfide, and groups formed by removing 1 to 3 hydrogen atoms from diphenyl sulfide.
[0027] The aromatic hydrocarbon group, aromatic heterocyclic group, or arylalkylene group may have one or more monovalent substituents. Examples of the monovalent substituent include a fluorine atom; a haloalkyl group such as a fluoromethyl group, a difluoromethyl group, or a trifluoromethyl group; a linear or branched alkyl group having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, or a tert-butyl group; a cyclic alkyl group having 5 to 7 carbon atoms, such as a cyclopentyl group, a cyclohexyl group, or a cycloheptyl group; a linear or branched alkoxy group having 1 to 20 carbon atoms, such as a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a tert-butoxy group, a pentyloxy group, a hexyloxy group, a heptyloxy group, or an octyloxy group; a nitro group; a cyano group; an alkylamino group having an alkyl group having 1 to 10 carbon atoms, such as a methylamino group, an ethylamino group, a dimethylamino group, or a diethylamino group; a cyclic amino group such as a pyrrolidino group, a piperidino group, or a morpholino group; aryl groups having 5 to 20 carbon atoms, which may be substituted with a halogen atom such as a fluorine atom, an alkyl group having 1 to 20 carbon atoms, an alkoxy group, an amino group, etc. (specific examples of the aryl group are the same as those of the aromatic hydrocarbon group described above); heterocyclic groups containing one or more of a nitrogen atom, a sulfur atom, and an oxygen atom having 4 to 20 carbon atoms, which may be substituted with a halogen atom such as a fluorine atom, an alkyl group having 1 to 20 carbon atoms, an alkoxy group, an amino group, etc. (The heterocyclic group may be one consisting of only one ring, or may be a compound in which a plurality of compounds consisting of only one aromatic heterocyclic ring are directly bonded to each other at one carbon atom, or may be a condensed heterocyclic group. Specific examples of the heterocyclic group include the specific examples of the aromatic heterocyclic group described above); ester groups, thioether groups, etc. These groups may be substituted with a halogen atom, a hetero element, an alkyl group, an aromatic ring, etc.
[0028] In the above general formula (1), n is an integer of 2 to 6, with 2 or 3 being preferred.
[0029] A specific example of the tetrafluorobenzoic acid derivative having the structure represented by the above general formula (1) is a compound represented by the following structural formula (3) (DF4CA-TT). [ka]
[0030] In the above general formula (2), R 2 and R 3 One of the groups is a carboxyl group, and the other is a fluorine group, a trifluoromethyl group, a cyano group, or a nitro group. A fluoronaphthalene dicarboxylic acid derivative having a structure represented by general formula (2) is a compound in which two hydrogen atoms on the naphthalene ring are substituted with carboxyl groups, five hydrogen atoms on the naphthalene ring are substituted with elemental fluorine, and the remaining hydrogen atom on the naphthalene ring is substituted with elemental fluorine, a trifluoromethyl group, a cyano group, or a nitro group.
[0031] A specific example of the fluoronaphthalenedicarboxylic acid derivative having the structure represented by the above general formula (2) is a compound (F6-DCA) represented by the following structural formula (4). [ka]
[0032] The compound represented by the above structural formula (4) may be used as a mixture with its isomers or as a pure substance.
[0033] The second material may be any material capable of transporting holes, and is preferably an organic material. More preferably, the second material is an organic material having a highest occupied molecular orbital (HOMO) level of 4.0 eV to 7.0 eV, and particularly preferably a p-type organic semiconductor material having a HOMO level of 4.5 eV to 6.0 eV. For example, any of the conventionally known materials shown below may be used as the material for the hole transport layer of an organic EL device, and among these, a material that satisfies the above HOMO level requirement is preferred. Also, various p-type polymeric materials and various p-type low molecular materials may be used alone or in combination.
[0034] Examples of the p-type polymeric material (organic polymer) include polyarylamine, fluorene-arylamine copolymer, fluorene-bithiophene copolymer, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophene, polyhexylthiophene, poly(p-phenylenevinylene), polytinylenevinylene, pyrene formaldehyde resin, ethylcarbazole formaldehyde resin, or derivatives thereof. These polymeric materials can also be used as mixtures with other compounds. As an example, a mixture containing polythiophene includes poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS).
[0035] Examples of the p-type low molecular weight material include arylcycloalkane compounds such as 1,1-bis(4-di-para-triaminophenyl)cyclohexane and 1,1'-bis(4-di-para-tolylaminophenyl)-4-phenyl-cyclohexane, 4,4',4"-trimethyltriphenylamine, N,N,N',N'-tetraphenyl-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD1), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD4), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD5), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD6), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD7), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD8), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD9), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4, N,N,N',N'-tetrakis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N,N',N'-tetrakis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), 4,4'-bis[N-phenyl-N-[4'-diphenylamino-1,1'-biphenyl-4-yl]amino]-1,1'-biphenyl (TPTE), and other arylamine compounds; N,N,N',N'-tetraphenyl-para- Phenylenediamine, N,N,N',N'-tetra(para-tolyl)-para-phenylenediamine, N,N,N',N'-tetra(meta-tolyl)-meta-phenylenediamine (PDA) and other phenylenediamine compounds, carbazole, N-isopropylcarbazole, N-phenylcarbazole and other carbazole compounds, stilbene, 4-di-para-tolylaminostilbene and other stilbene compounds, oxazole compounds such as OxZ, triphenylmethane, 4,4',4"-tris(N-3-methylphenyl-N-phenylamino)triphenyl amine (m-MTDATA) and other triphenylmethane compounds, pyrazoline compounds such as 1-phenyl-3-(para-dimethylaminophenyl)pyrazoline, benzine (cyclohexadiene) compounds, triazole compounds such as triazole, imidazole compounds such as imidazole, oxadiazole compounds such as 1,3,4-oxadiazole and 2,5-di(4-dimethylaminophenyl)-1,3,4-oxadiazole, anthracene compounds such as anthracene and 9-(4-diethylaminostyryl)anthracene, fluorenone, 2,4,Fluorenone compounds such as 7-trinitro-9-fluorenone and 2,7-bis(2-hydroxy-3-(2-chlorophenylcarbamoyl)-1-naphthylazo)fluorenone, aniline compounds such as polyaniline, silane compounds, pyrrole compounds such as 1,4-dithioketo-3,6-diphenyl-pyrrolo-(3,4-c)pyrrolopyrrole, fluorene compounds such as fluorene, porphyrin compounds such as porphyrin and metal tetraphenylporphyrin, quinacridone compounds such as quinacridone, fluorene compounds such as fluorene, fluorene compounds such as fluorene, fluorene compounds such as fluorene, fluorine compounds such as fluorine ... Examples of suitable compounds include metal or non-metal phthalocyanine compounds such as phthalocyanine, copper phthalocyanine, tetra(t-butyl)copper phthalocyanine, and iron phthalocyanine; metal or non-metal naphthalocyanine compounds such as copper naphthalocyanine, vanadyl naphthalocyanine, and monochlorogallium naphthalocyanine; and benzidine compounds such as N,N'-di(naphthalene-1-yl)-N,N'-diphenyl-benzidine and N,N,N',N'-tetraphenylbenzidine. One or more of these compounds may be used. Among these, arylamine compounds such as TPTE are particularly preferred.
[0036] The organic thin film of the present embodiment may be a single film containing a first material, which is a tetrafluorobenzoic acid derivative having a structure represented by general formula (1) and / or a fluoronaphthalenedicarboxylic acid derivative having a structure represented by general formula (2), and a second material that transports holes, or may be a laminated film of a film containing the first material and a film containing the second material. Whether it is a single film or a laminated film, it can be manufactured by a vapor deposition process, and by applying it to an organic EL element, the driving voltage of the organic EL element can be reduced and the driving stability can be improved.
[0037] The ratio of the first material to the second material contained in the organic thin film of this embodiment is not particularly limited and can be appropriately determined depending on the type of compound used for each of the first material and the second material. The ratio of the first material to the second material is preferably 0.1:99.9 to 1:1 in mass ratio (first material:second material), more preferably 0.5:99.5 to 1:2, and even more preferably 1:99 to 1:3. When the ratio is as above, the effect of improving hole transportability and hole injection property due to the inclusion of the first material and the second material in the organic thin film becomes significant.
[0038] The organic thin film is preferably formed by a vacuum deposition method such as resistance heating. When the organic thin film is manufactured by a vapor deposition process, it can be manufactured by the same method as when other layers constituting an organic EL element are manufactured by a vapor deposition process, and the first material and the second material may be simultaneously vapor-deposited or sequentially vapor-deposited. When vapor-deposited sequentially, either the first material or the second material may be vapor-deposited first. In addition, either one may be vapor-deposited first and then both may be vapor-deposited, or either one may be vapor-deposited first. Such a method for manufacturing an organic thin film including a step of simultaneously vapor-depositing a first material which is a tetrafluorobenzoic acid derivative having a structure represented by the above general formula (1) and / or a first material which is a fluoronaphthalenedicarboxylic acid derivative having a structure represented by the above general formula (2) and a second material which transports holes on a surface on which the organic thin film is to be formed is one of the preferred embodiments of the method for manufacturing an organic thin film of the present invention. In addition, a method for producing an organic thin film comprising a step of first depositing either a first material or a second material onto a surface on which an organic thin film is to be formed, and then depositing the other material or both of the materials, or a method for producing an organic thin film comprising a step of simultaneously depositing a first material and a second material onto a surface on which an organic thin film is to be formed, and then depositing either the first material or the second material onto the surface on which an organic thin film is to be formed, is also one of suitable embodiments of the method for producing an organic thin film of the present invention.
[0039] [Organic EL element] The organic electroluminescent device according to one embodiment of the present invention is characterized in that it has an emitting layer between a cathode and an anode, and has a layer between the anode and the emitting layer, the layer containing a first material which is a tetrafluorobenzoic acid derivative having a structure represented by the above general formula (1).
[0040] In addition, the organic electroluminescence element of another embodiment of the present invention is characterized in that it has an emitting layer between a cathode and an anode, and has a layer containing the above-mentioned material for organic electroluminescence elements (in other words, a layer containing a first material which is a fluoronaphthalenedicarboxylic acid derivative having a structure represented by the above general formula (2)) between the anode and the emitting layer.
[0041] These organic EL elements of the present embodiment use the above-mentioned tetrafluorobenzoic acid derivative having the structure represented by the general formula (1) or the fluoronaphthalenedicarboxylic acid derivative having the structure represented by the general formula (2), which are not easily decomposed by heating, have excellent storage stability, and have relatively low acidity. Therefore, they can be manufactured by a vapor deposition process, and have a low driving voltage and excellent driving stability.
[0042] The organic EL device of the present embodiment preferably has a laminated film of a layer containing the first material and a layer containing a second material that transports holes between the anode and the light-emitting layer, which further reduces the driving voltage and improves driving stability. Here, either the layer containing the first material or the layer containing the second material may be disposed on the anode side, but it is preferable that the layer containing the first material is disposed on the anode side, that is, it is preferable to have a layer containing the second material between the light-emitting layer and the layer containing the first material.
[0043] In addition, the organic EL element of the present embodiment preferably has a layer containing the first material and a second material transporting holes between the anode and the light-emitting layer, and a layer containing the second material between the light-emitting layer and the layer containing the first material and the second material, which further reduces the driving voltage and improves driving stability.
[0044] Next, the organic EL device of the present invention will be described in detail with reference to examples. Fig. 1 is a schematic cross-sectional view for explaining one example of the organic EL element of the present invention. The organic EL element 1 of this embodiment shown in Fig. 1 has an emitting layer 6 between an anode 3 and a cathode 9. The organic EL element 1 shown in Fig. 1 has a hole injection layer 4 between the anode 3 and the emitting layer 6, the hole injection layer 4 containing the organic thin film of the present invention, or a first material which is a tetrafluorobenzoic acid derivative having the structure represented by the above general formula (1), or a first material which is a fluoronaphthalenedicarboxylic acid derivative having the structure represented by the above general formula (2). The organic EL element 1 of this embodiment has a laminated structure in which an anode 3, a hole injection layer 4, a hole transport layer 5, a light-emitting layer 6, an electron transport layer 7, an electron injection layer 8, and a cathode 9 are formed in this order on a substrate 2.
[0045] The organic EL element 1 shown in FIG. 1 may be of a top emission type in which light is extracted from the side opposite to the substrate 2, or of a bottom emission type in which light is extracted from the substrate 2 side.
[0046] (substrate) Examples of the material for the substrate 2 include a resin material, a glass material, etc. The material for the substrate 2 may be one type alone or a combination of two or more types. Examples of the resin material used for the substrate 2 include polyethylene terephthalate, polyethylene naphthalate, cycloolefin polymer, polyamide, polyethersulfone, polymethyl methacrylate, polycarbonate, polyarylate, etc. When a resin material is used as the material for the substrate 2, it is preferable because an organic EL element 1 having excellent flexibility can be obtained. On the other hand, examples of the glass material used for the substrate 2 include quartz glass and soda glass.
[0047] When the organic EL element 1 is of a bottom emission type, the material of the substrate 2 is a transparent substrate. On the other hand, when the organic EL element 1 is of a top emission type, not only a transparent substrate but also an opaque substrate may be used as the material of the substrate 2. Examples of opaque substrates include a substrate made of a ceramic material such as alumina, a substrate in which an oxide film (insulating film) is formed on the surface of a metal plate such as stainless steel, and a substrate made of a resin material.
[0048] The average thickness of the substrate 2 can be determined depending on the material of the substrate 2, and is preferably 0.1 to 30 mm, and more preferably 0.1 to 10 mm. The average thickness of the substrate 2 can be measured with a digital multimeter and a vernier caliper.
[0049] (electrode) In the organic EL element 1 of the present embodiment, the anode 3 and the cathode 9 may be made of known conductive materials as appropriate, but it is preferable that at least one of them is transparent in order to extract light. Examples of known transparent conductive materials include ITO (tin-doped indium oxide), ATO (antimony-doped indium oxide), IZO (indium-doped zinc oxide), AZO (aluminum-doped zinc oxide), and FTO (fluorine-doped indium oxide). On the other hand, examples of opaque conductive materials include calcium, magnesium, aluminum, barium, tin, indium, copper, silver, ytterbium, and alloys thereof. Of these, ITO, IZO, and FTO are preferable for the anode 3. On the other hand, among these, Al and AgMg alloys are preferable for the cathode 9.
[0050] The average thickness of the anode 3 is not particularly limited, but is preferably 10 to 500 nm, and more preferably 70 to 200 nm. The average thickness of the anode 3 can be measured by a stylus step gauge or spectroscopic ellipsometry.
[0051] The average thickness of the cathode 9 is not particularly limited, but is preferably 10 to 1000 nm, and more preferably 30 to 150 nm. Even when an opaque material is used, the cathode 9 can be used as a top emission type or transparent type cathode 9 by setting the average thickness to, for example, about 10 to 30 nm. The average thickness of the cathode 9 can be measured during film formation using a quartz crystal film thickness meter.
[0052] (Hole injection layer) The hole injection layer 4 can have the same structure as the organic thin film described above, and this structure makes it possible to form a hole injection layer 4 with improved hole injection properties and stability. Also, a part of the organic thin film described above may be the hole injection layer 4, and another part of the organic thin film may be the hole transport layer 5 described later. For example, a mixed film of the first material and the second material may be the hole injection layer 4, and a film made of the second material may be the hole transport layer 5, a film made only of the first material may be the hole injection layer 4, and a film made only of the second material may be the hole transport layer 5, a laminated film of the second material and the first material may be the hole injection layer 4, and a film made only of the second material may be the hole transport layer 5, or a mixed film of the first material and the second material may be the hole injection layer 4 and hole transport layer 5. In addition, when the hole injection layer 4 contains a first material (dopant) and a second material (host material), the mass ratio of the first material to the second material (first material:second material) is preferably 0.1:99.9 to 1:1, and more preferably 1:99 to 1:2.
[0053] The average thickness of the hole injection layer 4 is not particularly limited, but is preferably from 1 to 1000 nm, and more preferably from 5 to 50 nm. The average thickness of the hole injection layer 4 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry.
[0054] (Hole transport layer) Any compound that can be generally used as a material for a hole transport layer can be used as the material for the hole transport layer 5, and various p-type polymeric materials and various p-type low molecular weight materials can be used alone or in combination. For example, the various materials exemplified as the second material for the organic thin film described above can be used.
[0055] Examples of the p-type polymeric material (organic polymer) include polyarylamine, fluorene-arylamine copolymer, fluorene-bithiophene copolymer, poly(N-vinylcarbazole), polyvinylpyrene, polyvinylanthracene, polythiophene, polyalkylthiophene, polyhexylthiophene, poly(p-phenylenevinylene), polytinylenevinylene, pyrene formaldehyde resin, ethylcarbazole formaldehyde resin, or derivatives thereof. These polymeric materials can also be used as mixtures with other compounds. As an example, a mixture containing polythiophene includes poly(3,4-ethylenedioxythiophene / styrenesulfonic acid) (PEDOT / PSS).
[0056] Examples of the p-type low molecular weight material include arylcycloalkane compounds such as 1,1-bis(4-di-para-triaminophenyl)cyclohexane and 1,1'-bis(4-di-para-tolylaminophenyl)-4-phenyl-cyclohexane, 4,4',4"-trimethyltriphenylamine, N,N,N',N'-tetraphenyl-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD1), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD4), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD5), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD6), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD7), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD8), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD9), N,N'-diphenyl-N,N'-bis(4-methylphenyl)-1,1'-biphenyl-4, N,N,N',N'-tetrakis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD2), N,N,N',N'-tetrakis(4-methoxyphenyl)-1,1'-biphenyl-4,4'-diamine (TPD3), N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4,4'-diamine (α-NPD), 4,4'-bis[N-phenyl-N-[4'-diphenylamino-1,1'-biphenyl-4-yl]amino]-1,1'-biphenyl (TPTE), and other arylamine compounds; N,N,N',N'-tetraphenyl-para- Phenylenediamine, N,N,N',N'-tetra(para-tolyl)-para-phenylenediamine, N,N,N',N'-tetra(meta-tolyl)-meta-phenylenediamine (PDA) and other phenylenediamine compounds, carbazole, N-isopropylcarbazole, N-phenylcarbazole and other carbazole compounds, stilbene, 4-di-para-tolylaminostilbene and other stilbene compounds, oxazole compounds such as OxZ, triphenylmethane, 4,4',4"-tris(N-3-methylphenyl-N-phenylamino)triphenyl amine (m-MTDATA) and other triphenylmethane compounds, pyrazoline compounds such as 1-phenyl-3-(para-dimethylaminophenyl)pyrazoline, benzine (cyclohexadiene) compounds, triazole compounds such as triazole, imidazole compounds such as imidazole, oxadiazole compounds such as 1,3,4-oxadiazole and 2,5-di(4-dimethylaminophenyl)-1,3,4-oxadiazole, anthracene compounds such as anthracene and 9-(4-diethylaminostyryl)anthracene, fluorenone, 2,4,Fluorenone compounds such as 7-trinitro-9-fluorenone and 2,7-bis(2-hydroxy-3-(2-chlorophenylcarbamoyl)-1-naphthylazo)fluorenone, aniline compounds such as polyaniline, silane compounds, pyrrole compounds such as 1,4-dithioketo-3,6-diphenyl-pyrrolo-(3,4-c)pyrrolopyrrole, fluorene compounds such as fluorene, porphyrin compounds such as porphyrin and metal tetraphenylporphyrin, quinacridone compounds such as quinacridone, fluorene compounds such as fluorene, fluorene compounds such as fluorene, fluorene compounds such as fluorene, fluorine compounds such as fluorine ... Examples of suitable compounds include metal or non-metal phthalocyanine compounds such as phthalocyanine, copper phthalocyanine, tetra(t-butyl)copper phthalocyanine, and iron phthalocyanine; metal or non-metal naphthalocyanine compounds such as copper naphthalocyanine, vanadyl naphthalocyanine, and monochlorogallium naphthalocyanine; and benzidine compounds such as N,N'-di(naphthalene-1-yl)-N,N'-diphenyl-benzidine and N,N,N',N'-tetraphenylbenzidine. One or more of these compounds may be used. Among these, arylamine compounds such as TPTE are particularly preferred.
[0057] The average thickness of the hole transport layer 5 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the hole transport layer 5 can be measured by, for example, a stylus step gauge or spectroscopic ellipsometry.
[0058] (Light Emitting Layer) In the organic EL element 1 of the present embodiment, the material forming the light-emitting layer 6 may be a low molecular weight compound or a high molecular weight compound, or a mixture of these may be used. In the present invention, the low molecular weight material means a material that is not a high molecular weight material (polymer), and does not necessarily mean an organic compound with a low molecular weight.
[0059] Examples of polymeric materials for forming the light-emitting layer 6 include polyacetylene-based compounds such as trans-polyacetylene, cis-polyacetylene, poly(diphenylacetylene) (PDPA), and poly(alkyl, phenylacetylene) (PAPA); poly(para-phenylenevinylene) (PPV), poly(2,5-dialkoxy-para-phenylenevinylene) (RO-PPV), cyano-substituted-poly(para-phenylenevinylene) (CN-PPV), poly( Polyparaphenylenevinylene compounds such as 2-dimethyloctylsilyl-paraphenylenevinylene) (DMOS-PPV) and poly(2-methoxy,5-(2'-ethylhexoxy)-paraphenylenevinylene) (MEH-PPV); polythiophene compounds such as poly(3-alkylthiophene) (PAT) and poly(oxypropylene)triol (POPT); poly(9,9-dialkylfluorene) (PDAF) and poly(dioctylfluorene) Polyfluorene compounds such as α,ω-bis[N,N'-di(methylphenyl)aminophenyl]-poly[9,9-bis(2-ethylhexyl)fluorene-2,7-dyl] (PF2 / 6am4), poly(9,9-dioctyl-2,7-divinylenefluorenyl-ortho-co(anthracene-9,10-diyl); poly(para-phenylene) (PPP), poly(1,5-dialkoxy- ... Examples of suitable polymeric materials include polyparaphenylene-based compounds such as poly(paraphenylene) (RO-PPP) and the like; polycarbazole-based compounds such as poly(N-vinylcarbazole) (PVK) and the like; polysilane-based compounds such as poly(methylphenylsilane) (PMPS), poly(naphthylphenylsilane) (PNPS) and poly(biphenylylphenylsilane) (PBPS) and the like; and further examples of suitable polymeric materials include boron compound-based polymeric materials described in JP-A-2011-184430 and JP-A-2012-151148.
[0060] Examples of low molecular weight materials for forming the light emitting layer 6 include a three-coordinate iridium complex having 2,2'-bipyridine-4,4'-dicarboxylic acid as a ligand, and factorys(2-phenylpyridine)iridium (Ir(ppy) 3 ), 8-hydroxyquinoline aluminum (Alq 3), tris(4-methyl-8-quinolinolato)aluminum(III) (Almq 3 ), 8-hydroxyquinoline zinc (Znq 2 ), (1,10-phenanthroline)-tris-(4,4,4-trifluoro-1-(2-thienyl)-butane-1,3-dionate) europium(III) (Eu(TTA) 3(phen)), 2,3,7,8,12,13,17,18-octaethyl-21H,23H-porphine platinum(II) and other metal complexes; benzene-based compounds such as distyrylbenzene (DSB) and diaminodistyrylbenzene (DADSB); naphthalene-based compounds such as naphthalene and Nile Red; phenanthrene-based compounds such as phenanthrene; chrysene-based compounds such as chrysene and 6-nitrochrysene; perylene, N,N'-bis(2,5-di-t-butylphenyl)-3,4,9,10-perylene-dicarbonyl; perylene compounds such as bis(styrylanthracene) and the like, coronene compounds such as coronene, anthracene compounds such as anthracene and bisstyrylanthracene, pyrene compounds such as pyrene, pyran compounds such as 4-(di-cyanomethylene)-2-methyl-6-(para-dimethylaminostyryl)-4H-pyran (DCM) and the like, acridine compounds such as acridine, stilbene compounds such as stilbene, 4,4'-bis[9-dicarbazolyl]-2,2'-biphenyl (CBP), 4,4'-bis(9-ethyl-3-carbazolyl)-2,2'-biphenyl (CBP), carbazole compounds such as 2,5-dibenzoxazolethiophene; thiophene compounds such as 2,5-dibenzoxazolethiophene; benzoxazole compounds such as benzoxazole; benzimidazole compounds such as benzimidazole; benzothiazole compounds such as 2,2'-(para-phenylenedivinylene)-bisbenzothiazole; butadiene compounds such as bistyryl(1,4-diphenyl-1,3-butadiene) and tetraphenylbutadiene; naphthalimide compounds such as naphthalimide; mido compounds, coumarin compounds such as coumarin, perinone compounds such as perinone, oxadiazole compounds such as oxadiazole, aldazine compounds, cyclopentadiene compounds such as 1,2,3,4,5-pentaphenyl-1,3-cyclopentadiene (PPCP), quinacridone compounds such as quinacridone and quinacridone red, pyridine compounds such as pyrrolopyridine and thiadiazolopyridine, spiro compounds such as 2,2',7,7'-tetraphenyl-9,9'-spirobifluorene, phthalocyanine (H 2Pc), metal or non-metal phthalocyanine compounds such as copper phthalocyanine, and boron compound materials described in JP-A-2009-155325 and JP-A-5660371, and one or more of these can be used. Quantum dots and perovskite materials can also be used as the light-emitting layer.
[0061] The average thickness of the light-emitting layer 6 is not particularly limited, but is preferably from 10 to 150 nm, and more preferably from 20 to 100 nm. The average thickness of the light-emitting layer 6 may be measured by a stylus-type step gauge, or may be measured by a quartz crystal thickness gauge during the deposition of the light-emitting layer 6.
[0062] (electron transport layer) As the material for the electron transport layer 7, a wide variety of known materials capable of transporting electrons can be used. Specifically, phenyl-dipyrenylphosphine oxide (POPy 2), pyridine derivatives such as tris-1,3,5-(3'-(pyridin-3"-yl)phenyl)benzene (TmPhPyB), quinoline derivatives such as (2-(3-(9-carbazolyl)phenyl)quinoline (mCQ)), pyrimidine derivatives such as 2-phenyl-4,6-bis(3,5-dipyridylphenyl)pyrimidine (BPyPPM), pyrazine derivatives, phenanthroline derivatives such as bathophenanthroline (BPhen), 2,4-bis(4-biphenyl)-6-(4'-(2-pyridinyl)-4-biphenyl)-[1,3,5]triazine (MPT), 2,4,6-tris(m-pyridin-3-yl-phenyl)pyrimidine (BPyPPM), triazine derivatives such as 3-phenyl-4-(1'-naphthyl)-5-phenyl-1,2,4-triazole (TAZ), triazole derivatives such as 2-(4-biphenylyl)-5-(4-tert-butylphenyl-1,3,4-oxadiazole) (PBD), imidazole derivatives such as 2,2',2"-(1,3,5-benzotriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBI), aromatic ring tetracarboxylic anhydrides such as naphthalene and perylene, bis[2-(2-hydroxyphenyl)benzothiazolato]zinc (Zn(BTZ) 2 ), tris(8-hydroxyquinolinato)aluminum (Alq 3 ), organosilane derivatives such as silole derivatives such as 2,5-bis(6'-(2',2"-bipyridyl-1,1-dimethyl-3,4-diphenylsilole (PyPySPyPy), and boron-containing compounds described in JP-A-2013-239691, WO 2014 / 133141, JP-A-2016-172728, JP-A-2016-199507, and JP-A-2016-199508. One or more of these may be used.
[0063] The average thickness of the electron transport layer 7 is not particularly limited, but is preferably 10 to 150 nm, and more preferably 20 to 100 nm. The average thickness of the electron transport layer 7 can be measured by a stylus step gauge or spectroscopic ellipsometry.
[0064] (electron injection layer) The material used for the electron injection layer 8 is selected from the viewpoints of the work function of the cathode 9 and the LUMO level of the electron transport layer 7. When the electron transport layer 7 is not provided, the material is selected in consideration of the LUMO level of the material used for the light emitting layer 6. The material for the electron injection layer 8 may be an organic compound or an inorganic compound. When the electron injection layer 8 is made of an inorganic compound, for example, lithium fluoride, sodium fluoride, potassium fluoride, cesium fluoride, cesium carbonate, etc., in addition to alkali metals and alkaline earth metals, can be used. When the electron injection layer 8 is made of an organic compound, for example, 8-quinolinolatolithium (Liq) can be used.
[0065] The average thickness of the electron injection layer 8 can be from 1 nm to several μm, but is preferably 1 to 1000 nm, and more preferably 2 to 100 nm, from the viewpoint of obtaining an organic EL element that can be driven at a low voltage. The average thickness of the electron injection layer 8 can be measured by a stylus step gauge or spectroscopic ellipsometry.
[0066] (Formation method) The organic EL device 1 shown in FIG. 1 can be manufactured by forming an anode 3, a hole injection layer 4, a hole transport layer 5, a light emitting layer 6, an electron transport layer 7, an electron injection layer 8, and a cathode 9 in this order on a substrate 2. The method of forming each layer of the anode 3, the hole injection layer 4, the hole transport layer 5, the light emitting layer 6, the electron transport layer 7, the electron injection layer 8, and the cathode 9 is not particularly limited, and each layer can be formed by appropriately using various conventionally known formation methods according to the characteristics of the material used for each layer. Methods of forming each layer include chemical vapor deposition (CVD) such as plasma CVD, thermal CVD, and laser CVD, which are gas phase film formation methods, dry plating methods such as vacuum deposition, sputtering, and ion plating, and spraying methods, and wet plating methods such as electrolytic plating, immersion plating, and electroless plating, which are liquid phase film formation methods, and printing techniques such as the sol-gel method, MOD method, spray pyrolysis method, doctor blade method using a fine particle dispersion, spin coating method, inkjet method, and screen printing method. It is preferable to select these methods depending on the characteristics of the material of each layer, and the manufacturing method may differ for each layer.
[0067] The organic EL element 1 of the present embodiment can change the emission color by appropriately selecting the material of the light-emitting layer 6, and can also obtain a desired emission color by using a color filter or the like in combination. Therefore, the organic EL element of the present invention can be suitably used in display devices and lighting devices.
[0068] (Other examples) The organic EL element of the present invention is not limited to the organic EL element described in the above-mentioned embodiment. Specifically, in the above-described embodiment, the organic EL element 1 having a forward structure in which the anode 3 is disposed between the substrate 2 and the light-emitting layer 6 has been described as an example, but the organic EL element of the present invention may have an inverted structure in which the cathode is disposed between the substrate and the light-emitting layer.
[0069] In the organic EL device of the present invention, the hole transport layer, the electron transport layer and the electron injection layer may be formed as necessary, and may not be provided. In addition, each layer of the anode, hole injection layer, hole transport layer, light-emitting layer, electron transport layer, electron injection layer, and cathode may be formed of a single layer or may be composed of two or more layers. In addition, the organic EL element of the present invention may have other layers between each layer of the anode, hole injection layer, hole transport layer, light-emitting layer, electron transport layer, electron injection layer, and cathode. Specifically, for reasons such as further improving the characteristics of the organic EL element, an electron blocking layer or the like may be provided as necessary.
[0070] [Display device] The display device of the present invention is characterized by including the above-described organic electroluminescence element. Since the display device of the present invention includes an organic EL element having a low driving voltage and excellent driving stability as described above, it has a low driving voltage and excellent driving stability. In addition to the above-described organic electroluminescence element, the display device of the present invention can include other components generally used in display devices.
[0071] [Lighting device] The lighting device of the present invention is characterized by including the above-described organic electroluminescence element. Since the lighting device of the present invention includes an organic EL element having a low driving voltage and excellent driving stability as described above, it has a low driving voltage and excellent driving stability. In addition to the above-described organic electroluminescence element, the lighting device of the present invention can include other components generally used in lighting devices. [Examples]
[0072] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples at all.
[0073] [NMR measurement method] JEOL's AL400 was used. The spectrometer is an AL-Series spectrometer, and the probe is a TH5ATFG2 probe.
[0074] [Synthesis method of compound (DF4CA-TT) represented by structural formula (3)] A 100 mL reactor was charged with bistrimethylstannylbithiophene (1.2 g, 2.57 mmol, 1.0 eq.), methyl 4-bromo-2,3,5,6-tetrafluorobenzoate (1.85 g, 6.44 mmol, 2.5 eq.), (Ph 3 P) 4 Pd (89 mg, 0.773 mmol, 0.03 eq.) and deoxygenated anhydrous toluene (25 mL) were added. The solution was heated to 110°C and stirred for 18 hours. The suspension was allowed to cool, hexane (20 mL) was added, and the precipitated solid was separated. The filter bed was washed with ethanol and dried at 60°C under high vacuum to obtain a beige powder (1.09 g). Chlorobenzene (350 mL) was added, heated to 130°C, scavenger (Kyoward 1000) (1.1 g) was added and stirred, the suspension was filtered through Celite so that the temperature did not fall below 100°C, the filter bed was washed with heated chlorobenzene (50 mL), and the filtration part was allowed to cool as it was. The filter bed was dispersed and washed with chlorobenzene (80 mL) heated to 130°C, Galleon Earth V2R (2 g) was added, stirred for 5 minutes, and filtered through Celite when the internal temperature was 80°C or higher. The filtrates were combined and left to stand for 16 hours, and the precipitated solid was filtered off. The filter bed was washed with ethyl acetate and ethanol in that order. The solid was dried under high vacuum at 80°C to obtain an orange powder (0.78 g). 19 F-NMR, 1 H-NMR confirmed that the compound was the compound represented by the following structural formula (5). Next, the compound represented by structural formula (5) (0.76 g, 0.923 mmol, 1.0 eq.), 4N NaOH aqueous solution (7.06 mL, 28.2 mmol, 20 eq.), and THF (156 mL) were added to a 500 mL reactor. The mixture was stirred at a bath temperature of 75 ° C. for 36 hours. After cooling, 2N HCl aqueous solution (15 mL) was slowly dropped into the yellow suspension to obtain an acidic yellow solution. Distilled water (200 mL) was added to the solution, and the precipitated solid was filtered through a membrane, and the filter bed was washed with distilled water until the washing liquid became neutral, followed by washing with a small amount of methanol and drying at 60 ° C. under high vacuum to obtain an orange powder (0.62 g). This solid was washed successively with heated acetonitrile, ethyl acetate, and acetone, and further washed by heating and dispersion with THF, and heated at 90°C under high vacuum to obtain a compound (DF4CA-TT) (0.5 g, 0.953 mmol) represented by the following structural formula (3). The purity measured by HPLC was 90.1%. The synthesis scheme is as follows. The synthesized product was 19 F-NMR, 1 This was confirmed by H-NMR (Figures 2 and 3). [ka]
[0075] <Method for synthesizing the compound (F6-DCN) represented by structural formula (4)> Under an argon atmosphere, octafluoronaphthalene (5.0 g, 18.3 mmol, 1.0 eq.) and anhydrous diethyl ether (50 mL) were added to a 200 mL reactor. 2 O solution (35.1 mL, 38.6 mmol, 2.1 eq.) was added over 15 minutes, and the mixture was stirred for 1 hour. The cooling bath was then removed and the mixture was stirred at room temperature for 14 hours. The solution was quenched with 3% aqueous ammonium chloride solution (50 mL), and the organic and aqueous layers were separated. The aqueous layer was extracted with hexane / ethyl acetate = 1 / 1 (100 mL x 2), and the organic layers were combined, washed with tap water and saturated saline, dried, and concentrated to obtain a pale yellow solid (6.92 g). This was purified by column purification (SiO 2The resulting mixture was heated (55 g, heated heptane only) to obtain a colorless solid compound represented by the following structural formula (6) (4.35 g, 16.4 mmol, 89%). 19 F-NMR, 1 Analysis by 1 H-NMR revealed that it was a mixture of 1,6- and 1,7-substituted compounds. Next, the compound represented by structural formula (6) (4.35 g, 16.5 mmol, 1.0 eq.), NBS (8.79 g, 49.4 mmol, 3.0 eq.), BPO (1.06 g, 3.29 mmol, 0.2 eq.), and carbon tetrachloride (60 mL) were added to a 100 mL reactor. The suspension was heated to 75°C and stirred at the same temperature for 18 hours. After cooling, the suspension was poured into city water (100 mL) and chloroform (100 mL) was added to separate into two layers. The aqueous layer was extracted with chloroform (50 mL), and the organic layer was combined and washed with city water and saturated saline, dried over sodium sulfate, and concentrated to obtain a brown solid (8.9 g). This was purified by column purification (SiO 2 =100g, heptane / chloroform = 1 / 1) to obtain a colorless solid (5.76g, 13.6mmol, 82%). Next, this colorless solid (3.7g, 8.77mmol, 1.0eq.), sodium acetate (1.8g, 21.9mmol, 2.5eq.), 18-crown 6-ether (0.463g, 1.75mmol, 0.2eq.), and anhydrous acetonitrile (40mL) were added to a 100mL reactor. The suspension was heated to a bath temperature of 80°C and stirred at the same temperature for 12 hours. After cooling, the suspension was concentrated, and city water (30mL) and ethyl acetate (30mL) were added to the residue to separate it into two layers. The aqueous layer was extracted with ethyl acetate (25mL), and the organic layer was combined, washed with city water and saturated saline, dried, and then concentrated to obtain a reddish-black powder (3.27g). This was purified by column (SiO 2 = 120 g, heptane / ethyl acetate = 4 / 1 → 3 / 1) to obtain a colorless solid compound represented by the following structural formula (7) (2.29 g, 6.02 mmol, 68%, a mixture of 1,6- and 1,7-substituted compounds). The compound represented by structural formula (7) (2.29 g, 6.02 mmol, 1 eq.), THF (23 mL), and 4N-NaOH aqueous solution (6 mL, 24.1 mmol, 4.0 eq.) were added to a 100 mL reactor, and the mixture was stirred at a bath temperature of 60°C for 6 hours. After cooling, 10% ammonium chloride aqueous solution (20 mL) and ethyl acetate (50 mL) were added to the solution, and the solution was separated into two layers. The aqueous layer was extracted with ethyl acetate (25 mL), and the organic layer was combined, washed with tap water and saturated saline solution in that order, dried, and concentrated to obtain a reddish-black brown powder (2.41 g). This was purified by column purification (NH-SiO 2 =50g, heptane / ethyl acetate = 1 / 1 → 1 / 2) to obtain a colorless solid (1.19g, 4.01mmol, 66%). Next, this solid (1.19g, 4.02mmol, 1.0eq.) and acetone (30mL) were added to a 100mL reactor. Jones reagent was added dropwise to this suspension until the content turned reddish brown (ca.8g, excess). After stirring at room temperature for 2 hours, 2-propanol was added until the content turned pale yellow, and the mixture was stirred at the same temperature for 2 hours. City water (80mL) and diethyl ether (80mL) were added to this, and the mixture was separated into two layers. The aqueous layer was extracted with diethyl ether (50mL), and the organic layer was combined and washed with city water and saturated saline, dried, and concentrated to obtain a pale yellow powder (1.36g). This powder was dissolved by heating in acetonitrile (20 mL), the insoluble solid was filtered through a membrane while still hot, the filtered solution was concentrated to half its volume, chloroform (10 mL) was added, the mixture was stirred, the precipitated solid was filtered, the filtrate was concentrated, acetonitrile (5 mL) was added to the residue, the mixture was heated and stirred, the mixture was allowed to cool, and then the mixture was filtered. The filter bed was dispersed and washed with acetone, and the mixture was dried under high vacuum at 60°C for 3 hours to obtain a compound (F6-DCN) (0.52 g, 1.60 mmol) represented by the following structural formula (4). The purity measured by HPLC was 88.6%. The synthesis scheme is as follows. The synthesized product was 19 F-NMR, 1 This was confirmed by H-NMR (Figures 4 and 5). [ka]
[0076] Example 1 <Manufacturing of organic EL elements> Organic EL element 1 was produced by the following method. A commercially available transparent glass substrate with an average thickness of 0.7 mm and a patterned electrode (anode 3) made of ITO with a thickness of 150 nm was prepared as the substrate 2. The substrate 2 having the anode 3 was ultrasonically cleaned in a weak alkaline cleaner, acetone, and isopropanol, and then subjected to UV ozone cleaning for 20 minutes. Thereafter, an annealing treatment was performed in the atmosphere at 150° C. for 30 minutes, and the substrate was then subjected to ozone cleaning. 2 The plasma was irradiated for 5 minutes. Next, the substrate 2 was fixed to a substrate holder in the chamber of the vacuum deposition device, and the inside of the chamber of the vacuum deposition device was filled with 2×10 -5 The pressure was reduced to 100 MPa, and a hole injection layer 4, a hole transport layer 5, a light emitting layer 6, an electron transport layer 7, an electron injection layer 8, and a cathode 9 were successively formed by a vacuum deposition method using resistance heating.
[0077] First, a compound (DF4CA-TT) represented by the above structural formula (3) was used as the first material (dopant) and a compound (TPTE) represented by the following structural formula (8) was used as the second material (host) to form a hole injection layer 4 made of a mixture of the first and second materials by co-evaporation to a thickness of 15 nm. At this time, the concentration of the first material was adjusted to 5 mass % of the entire hole injection layer 4. [ka]
[0078] Subsequently, a hole transport layer 5 made of a compound (α-NPD) represented by the following structural formula (9) was formed to a thickness of 35 nm. [ka]
[0079] Next, the compound represented by the following structural formula (10) (Zn(BTZ) 2 ) as a host, and a compound represented by the following structural formula (11) (Ir(piq) 3 The light-emitting layer 6 was formed by co-evaporating Ir(piq) 3was set to 6 mass % with respect to the entire light emitting layer 6 . [ka]
[0080] Next, on the substrate on which the light-emitting layer 6 had been formed, a compound (TmPPyTz) represented by the following structural formula (12) was deposited to a thickness of 50 nm, and a compound (Liq) represented by the following structural formula (13) was deposited to a thickness of 1.2 nm to form an electron transport layer 7 and an electron injection layer 8, respectively. [ka]
[0081] Next, a cathode 9 made of aluminum and having a thickness of 100 nm was formed on the substrate on which the electron injection layer 8 had been formed. The cathode 9 was formed using a stainless steel deposition mask so that the deposition surface would be in the shape of a strip with a width of 3 mm, and the light-emitting area of the fabricated organic EL element 1 was set to 9 mm 2 It was decided.
[0082] Example 2 An organic EL device 1 of Example 2 was obtained in the same manner as in Example 1, except that the first material (dopant) of the hole injection layer 4 was changed to a compound represented by the above structural formula (4) (F6-DCN, first material).
[0083] Example 3 An organic EL device 1 of Example 3 was obtained in the same manner as in Example 1, except that in Example 1, a layer of a compound represented by the above structural formula (3) (DF4CA-TT, first material) was formed to a thickness of 1 nm on an anode 3 made of ITO, and a layer of a compound represented by the above structural formula (5) (TPTE, second material) was formed to a thickness of 15 nm thereon to form a laminated layer as a hole injection layer 4.
[0084] Comparative Example 1 An organic EL device 1 of Comparative Example 1 was obtained in the same manner as in Example 1, except that a film of the compound represented by the above structural formula (5) (TPTE, second material) was formed to a thickness of 15 nm on an anode 3 made of ITO in Example 1 to serve as a hole injection layer 4.
[0085] <Measurement of the light-emitting properties of organic EL elements> A voltage was applied to the organic EL elements produced in Examples 1 to 3 and Comparative Example 1 using a Keithley 2400-type source meter, and the luminance was measured using a Konica Minolta LS-100 to examine the relationship between the applied voltage and the luminance, and the change over time in the luminance under a constant current density when the initial luminance was 1000 nits. The results are shown in Figures 6 and 7.
[0086] <Result> In all of Examples 1 to 3, organic EL elements having a lower driving voltage and a longer life than those in Comparative Example 1 were obtained. In particular, in Examples 1 and 2 in which the hole injection layer 4 was formed as a mixed film of the first material and the second material, in addition to lowering the voltage, a lifespan that was more than twice as long was achieved, which is considered to be due to the effects of the acidic material in reducing the voltage and lengthening the lifespan. [Industrial Applicability]
[0087] The organic thin film of the present invention can be used in organic electroluminescence devices, display devices, lighting devices, and the like. [Explanation of symbols]
[0088] 1: Organic EL (electroluminescence) element 2: Substrate 3:Anode 4: Hole injection layer 5: Hole transport layer 6: Light-emitting layer 7:Electron transport layer 8:Electron injection layer 9: Cathode
Claims
1. An organic thin film, characterized in that it is a single film containing a first material, which is a tetrafluorobenzoic acid derivative having a structure represented by the following general formula (1), and a second material that transports holes, or a laminated film of a film containing the first material and a film containing the second material. 【Chemistry 1】 (In general formula (1), R 1 represents an aromatic hydrocarbon group, an aromatic heterocyclic group, an aryl alkylene group, a divalent or trivalent cyclic hydrocarbon group which may have a substituent, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a sulfur atom; and n is an integer from 2 to 6.
2. The organic thin film according to claim 1 , wherein the first material is a tetrafluorobenzoic acid derivative in which n in the general formula (1) is 2 or 3.
3. An organic electroluminescence element having a light-emitting layer between a cathode and an anode, An organic electroluminescence element, comprising a layer between the anode and the light-emitting layer, the layer containing a first material which is a tetrafluorobenzoic acid derivative having a structure represented by the following general formula (1): 【Chemistry 2】 (In general formula (1), R 1 represents an aromatic hydrocarbon group, an aromatic heterocyclic group, an aryl alkylene group, a divalent or trivalent cyclic hydrocarbon group which may have a substituent, a group formed by combining two or more of these groups, or a group formed by combining one or more of these groups with a sulfur atom; and n is an integer from 2 to 6.
4. The organic electroluminescence device according to claim 3 , further comprising a laminate film of a layer including the first material and a layer including a second material that transports holes, between the anode and the light-emitting layer.
5. a layer including the first material and a second material that transports holes between the anode and the light-emitting layer; The organic electroluminescence device according to claim 3 , further comprising a layer containing the second material between the light emitting layer and the layer containing the first material and the second material.
6. An organic thin film, characterized in that it is a single film containing a first material, which is a fluoronaphthalene dicarboxylic acid derivative having a structure represented by the following general formula (2), and a second material that transports holes, or a laminated film of a film containing the first material and a film containing the second material. 【Chemistry 3】 (In general formula (2), R 2 and R 3 one of the groups is a carboxyl group, and the other is a fluorine group, a trifluoromethyl group, a cyano group, or a nitro group.
7. A material for an organic electroluminescence device, comprising a fluoronaphthalenedicarboxylic acid derivative having a structure represented by the following general formula (2): 【Chemistry 4】 (In general formula (2), R 2 and R 3 one of the groups is a carboxyl group, and the other is a fluorine group, a trifluoromethyl group, a cyano group, or a nitro group.
8. An organic electroluminescence element having a light-emitting layer between a cathode and an anode, 10. An organic electroluminescence device comprising a layer containing the material for an organic electroluminescence device according to claim 7 between the anode and the light-emitting layer.
9. A display device comprising the organic electroluminescence element according to any one of claims 3 to 5 and 8.
10. A lighting device comprising the organic electroluminescence element according to any one of claims 3 to 5 and 8.
Citation Information
Patent Citations
Organic electroluminescent element
JP2013219278A